Moderating effects of government environmental policies on green products toward consumer buying behavior - Saleem, Muhammad Usman (Advances in Social Sciences Research Journal, 2017)
Green marketing is the concept itself embodies the notion that the product of a given company is produced using environmentally friendly process. The down side is that the consumer need to be made aware regarding these initiatives by various companies and therefore labeling is of utmost importance. However, the question does arise whether the labeling is indeed because the company follows procedure or their packaging so that consumer can buy and they also satisfy the regulatory requirement as well. This study on consumer buying behavior is unique in nature, as no other study has been conducted before that is similar in nature. Hefei is a significant and upcoming tier-one city and central people government has started taking initiatives to uplift the city in a central economic zone. The study used policy as a moderator and there seems to be a unique effect of policy as the Chinese consumers is unlike any other as Chinese consumers are always well aware about their surroundings and very cautious about their consumables, therefore this is an ideal market where to check the component of policy. the result shows that the consumer in Hefei are having a high moral ethics and that helps develop their attitude towards becoming environmentally aware consumer. The moderation effect is also evident with the significance value .001 and shows that’s the more a consumer is aware about the policy and labeling the more they want to become environmentally responsible consumer. The consumer is showing a stronger awareness and the overall conclusion desired from this study leads the conclusion that the consumer of Hefei is different from the others and exhibits an environmentally friendly attitude.